ASPEK PSIKOSOSIAL, AKTIVITAS FISIK, DAN KONSUMSI MAKANAN LANSIA DI MASYRAKAT - Rusilanti Rusilanti; Clara Meliyanti Kusharto; Ekawati S. Wahyuni (Jurnal Gizi dan Pangan, 2006)
This research attempts to analyze psychosocial aspect, physical activity, and food consumption of the elderly living in the community dwelling.  Research locations were chosen purposively in three POSBINDU (The Services Post for Elderly) located at areal of Bogor City, namely: Kelurahan Budi Agung (represents city-high income society), Kelurahan Baranangsiang (city-moderate to low society), and Kelurahan Situ Gede (boundary between city to rural-low income society).  A simple random sampling was applied to select the subjects. One hundred ninety-seven (197) subjects aged range 60-85 years old (mean age 68.4 years) were selected in those places and completed the survey between August 2004-July 2006. A cross –sectional design and one point approach was followed (Singarimbun & Effendi, 1995). A structured questionnaire was developed to collect data about psychological aspects (family and community support; health behavior; level of depression; life satisfaction), and food consumption limited to some nutrients essensial for elderly. For physical activity assessment, each subject rated his/her capacity involved in housekeeping. A descriptive, Chi Square, One Way ANOVA and Tuckey tests were applied to analyze the data.  The research results showed that there is no significance difference among elderly in three sites in terms of psychological aspect. However, there are significance differences in health behavior and physical activity. The worst health behavior and physical activity conditions were found among elderly in Kelurahan Situ Gede caused by the social-economic differences. In terms of food consumption aspects, the significance differences exist in intake of vitamin A, vitamin B, and calcium among the subjects.